Virulence and biotype analyses of hessian fly (Diptera: Cecidomyiidae) populations from Texas, Louisiana, and Oklahoma - Garcés-Carrera, Sandra; Knutson, Allen; Wang, Haiyan; Giles, Kristopher L.; Huang, Fangneng; Whitworth, R. Jeffrey; Smith, C. Michael; Chen, Ming-Shun (My University, 2014)
Hessian fly, Mayetiola destructor (Say, 1817), is a major pest of wheat, and is controlled mainly through deploying fly-resistant wheat cultivars. The challenge for the plant resistance approach is that virulence of Hessian fly populations in the field is dynamic, and wheat cultivars may lose resistance within 6-8 yr. To ensure continuous success of host plant resistance, Hessian fly populations in the field need to be constantly monitored to determine which resistance genes remain effective in different geographic regions. This study investigated five Hessian fly populations collected from Texas, Louisiana, and Oklahoma, where infestation by Hessian fly has been high in recent years. Eight resistance genes, H12, H13, H17, H18, H22, H25, H26, and Hdic, were found to be highly effective against all tested Hessian fly populations in this region, conferring resistance to ≥80% of plants containing one of these resistance genes. The frequencies of biotypes virulent to resistance genes H13 (biotype vH13), H18 (vH18), H21 (vH21), H25 (vH25), H26 (vH26), and Hdic (vHdic) were determined, and were found to vary from population to population, ranging from 0 to 45%. A logistic regression model was established to predict biotype frequencies based on the correlation between the percentages of susceptible plants obtained in a virulence test and the log-odds of virulent biotype frequencies determined by a traditional approach.
Citation: Garces-Carerra, S. . . . & Chen, M. (2014). Virulence and Biotype Analyses of Hessian Fly (Diptera: Cecidomyiidae) Populations From Texas, Louisiana, and Oklahoma. Journal of Economic Entomology, 107(1), 417-423. https://doi.org/10.1603/EC13372
Keywords: Mayetiola destructor; Biotype; Wheat; Plant resistance; Hessian fly